Hardness and Surface Detail Reproduction of Gypsum Casts Retrieved from Addition Silicone Impressions Disinfected for Different Time Points - Sara Koosha; Shabnam Pourhaghani; Kimia Attar (Islamic Dental Association of Iran, 2017)
Background and Aim: Bacterial colonization occurs following contamination of impression materials with blood and saliva. However, not all disinfecting agents are compatible with the impression materials and may cause changes in the resultant casts. The purpose of this study was to assess the impact of various immersion time of addi-tion silicon impressions in different disinfecting solutions on the surface hardness and detail reproduction of gypsum casts. Materials and Methods: In this in vitro experiment, 84 addition silicone impressions were divided into seven groups (n=12). One group served as the control and the other groups were disinfected with 1% sodium hypochlorite, 2.4% glutaraldehyde, and 5% povidone-iodine for 5 and 30 minutes. Impressions were poured with type IV dental stone. The Knoop hardness value (KHN) was measured by microhardness tester. Surface detail reproduction, casts were inspected under a light microscope at X10 magnification. The surface hardness data was analyzed using two way ANOVA, Tuk-ey`s test, Dunnett`s, One way ANOVA and t-test. The detail reproduction results were analyzed using the Kruskal-Wallis test. Results: Immersion in povidone-iodine for 5 minutes and in sodium hypochlorite and glutaraldehyde for 30 minutes significantly lowered the KHN of resultant casts (P=0.001). No other significant differences were noted (P>0.05). No significant difference was found in detail reproduction between groups (P>0.05). Conclusion: Increasing the immersion time of impressions in povidone-iodine increased the hardness of casts. Thus, 5% povidone-iodine is a more suitable disinfecting solution for longer immersion time given that other properties of the casts are not affected.